EFFECTS OF BACTERIAL ENDOTOXIN ON METABOLISM : II. PROTEIN-CARBOHYDRATE BALANCE FOLLOWING CORTISONE. INHIBITION OF INTESTINAL ABSORPTION AND ADRENAL RESPONSE TO ACTH - Berry, L. Joe (The Rockefeller University Press, 1959)
Urinary nitrogen excretion over a 17 hour period without food and water was determined for mice poisoned with endotoxin and for control mice with and without the subcutaneous injection of 5 mg. cortisone acetate. Endotoxin did not alter the quantity of nitrogen excreted, compared with that of control mice, but in both groups of animals cortisone increased urinary nitrogen by the same amount. A balance between the quantity of protein catabolized (as estimated by increased urinary nitrogen excretion) and the total carbohydrate stored as a result of cortisone administration was found in fasted and in fed mice but not in endotoxin-poisoned mice. Endotoxin inhibited the motility of the gastrointestinal tract and blocked the absorption of food. Injections of ACTH in normal mice increased protein degradation and carbohydrate synthesis. In endotoxin-poisoned animals, ACTH failed to alter urinary nitrogen excretion and carbohydrate reserves. ACTH increased susceptibility to endotoxin. The number of heat-killed cells of S. typhimurium required to block the increase in urinary nitrogen caused by an injection of ACTH was found to be 10(8). A partial block was found with 5 x 10(7) cells but not with 10(5) cells. Mice infected with S. typhimurium excreted less than the normal amount of urinary nitrogen in response to ACTH 6 to 23 hours postinfection while normal amounts of nitrogen were eliminated 54 to 71 hours postinfection. The number of viable cells in the mice during the earlier period was less than the number of dead cells required to alter the nitrogen output, while the reverse was true during the later period.